Groundwater Hydrological Model Simulation (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focuses on the application of groundwater models developed with the aim of optimizing the management of water resources in urban environments, coastal areas, karst aquifers, and riparian zones, among other environments. The testing of innovative techniques applied to traditional models, including machine learning techniques, is of particular interest. Special attention is given to the application of tools for the evaluation of climate change effects on groundwater.